Sea buckthorn bioactive metabolites and their pharmacological potential in digestive diseases - Dong, WenChang; Tang, YuChen; Qiao, JiaLe; Dong, ZhiQiang; Cheng, Jie (Frontiers in Pharmacology, 2025)
Sea buckthorn is a botanical drug with a long history of medicinal use in treating digestive diseases. It is considered “a food with medicinal and edible homology”, meaning it has various application scenarios. Sea buckthorn is known to have numerous bioactivities, such as anti-inflammatory, flora-regulating, immunoregulating, intestinal protective, and anticancer properties, as a potential natural therapy for digestive diseases. In both in vitro and in vivo experiments, ranging from cell lines to animal models and human patients, sea buckthorn has shown beneficial effects on symptoms associated with digestive disease. This study reviews the main bioactive metabolites of sea buckthorn and discusses their pharmacological effects and mechanisms in treating digestive diseases. In particular, we highlight bioactive metabolites isolated from sea buckthorn, their effects on inflammation, cancer, anti-Helicobacter pylori, radiation, and gut microbiota, and their molecular mechanisms of action in clinical applications. This article provides insight into the benefits of sea buckthorn, encouraging academic research in this area and the expansion of sea buckthorn-based applications for digestive diseases.